Imaging and imagining the Neanderthal : the role of technical drawings in archaeology - Reybrouck, David van
Reconstruction drawings intended to illustrate the realities of prehistoric life can be famously revealing of preconceptions in the minds of the modern illustrator and of the researcher who briefs the illustrator. But are the less interpretative drawings whose purpose is to record the material evidence more neutral in their look? Nineteenth-century technical illustrations of the Neanderthal skull are unintentionally revealing of attitude.